پاکستان میں ٹیکسز کی عدم ادائیگی کے اسباب اور ان کا تدارک : اسلامی تعلیمات کی روشنی میں تحقیقی جائزہ : Reasons and Remedies of Non-Payment of Taxes in Pakistan (A Research Analysis in the Light of Teachings of Islam) - Nasrullah, Dr. Muhammad; Alazhari, Dr. Ali Akbar (Al-Irfan, 2024)
Islam provides guidance to its adherents regarding affairs of material as well as spiritual life. Its financial commandments eradicate economic inequality in the society. Economic durability can only be maintained through Islamic conceptions of Zakat and the prohibition of usuary. However, at certain times, when sources of revenue are insufficient to meet the governmental expenditures, then the state has the right to levy taxes and organize obligations on persons within its borders. A tax is one of the most important mandatory duties shouldered on the citizens by government so that it may cover the expenses of state w.r.t defense, administration, social well-being and other infrastructure. This study shows the arguments about the justification of taxation and its boundary as per commandments of Islam. This paper means to guess the effect of financial policy in connection with durability of economy of Pakistan. Majority of citizens of Pakistan are not willing to pay the taxes. The study shows the reasons of non-payments of taxes and its remedy as pet Islamic concept of taxation. Finally, it is concluded that present level of taxation in Pakistan needs to be revised carefully as this has negative and bad effects on financial activities in Pakistan. This study is fundamentally designed to express the needs and requirements of Tax collection of revenue for the country. This is qualitative research in which data is collected from secondary, books, articles and online sources.